Anesthesia for non-obstetric surgery during pregnancy in a tertiary referral center: a 16-year retrospective, matched case-control, cohort study. (August 2019) - Devroe, S.; Bleeser, T.; Van de Velde, M.; Verbrugge, L.; De Buck, F.; Deprest, J.; Devlieger, R.; Rex, S.
Highlights: Non-obstetric surgery requiring anesthesia in pregnancy had an incidence of 0.48%. Surgery under anesthesia in pregnancy was associated with preterm births and lower birth weights. Intra-abdominal surgery was the most commonly performed procedure. Preterm birth related to surgery was higher if performed during the third trimester. General (vs. regional) anesthesia was more often associated with low birth weight. Abstract: Introduction: This retrospective, matched case-control cohort study describes the incidence, indications, anesthesia techniques and outcomes of pregnancies complicated by surgery in a single tertiary-referral hospital. Methods: Retrospective review of the hospital records of 171 patients who had non-obstetric surgery in the current pregnancy, between 2001 and 2016. Pregnancy outcomes of these women were firstly compared with all contemporary non-exposed patients (n=35 411), and secondly with 684 non-exposed control patients, matched for age, time of delivery and parity. Results: The incidence of non-obstetric surgery during pregnancy was 0.48%, mostly performed during the second trimester (44%) and under general anesthesia (81%). Intra-abdominal surgery (44%) was the most commonly performed procedure, predominantly using laparoscopy (79%). Women undergoing surgery delivered earlier and more frequently preterm (25% vs. 17%, P =0.018); and birth weight was significantly lower [median (95% CI) 3.16 (3.06 to 3.26) vs. 3.27 (3.22 to 3.32) kg, P =0.044]. When surgery was performed under general anesthesia, low birth weight was more frequent (22% vs 6%, P =0.046). Overall pregnancy outcomes were neither influenced by trimester nor location (intra- vs extra-abdominal) of surgery. However, preterm birth rate secondary to surgery was higher for interventions during the third trimester, compared with other trimesters (10% vs 0, P <0.001). Conclusion: Pregnant women who underwent surgery delivered preterm more frequently and their babies had lower birth weights. Laparoscopic surgery did not increase the incidence of adverse pregnancy outcomes. General anesthesia was associated with low birth weight. Whether these associations suggest causation or reflect the severity of the underlying condition remains speculative.